2023
DOI: 10.3390/biology12091170
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Minimise the Bacterial Genome as a Free-Living Growing System

Honoka Aida,
Bei-Wen Ying

Abstract: Exploring the minimal genetic requirements for cells to maintain free living is an exciting topic in biology. Multiple approaches are employed to address the question of the minimal genome. In addition to constructing the synthetic genome in the test tube, reducing the size of the wild-type genome is a practical approach for obtaining the essential genomic sequence for living cells. The well-studied Escherichia coli has been used as a model organism for genome reduction owing to its fast growth and easy manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The present study first demonstrated ML-assisted medium specialization for differentiated bacterial growth. ML was remarkably significant in medium optimization for microbial and mammalian cells [26,31], which could be widely applied to synthetic construction and production [48,49]. The present study provides alternative applications in medium development for selective cultures.…”
Section: Discussionmentioning
confidence: 75%
“…The present study first demonstrated ML-assisted medium specialization for differentiated bacterial growth. ML was remarkably significant in medium optimization for microbial and mammalian cells [26,31], which could be widely applied to synthetic construction and production [48,49]. The present study provides alternative applications in medium development for selective cultures.…”
Section: Discussionmentioning
confidence: 75%
“…The present study first demonstrated ML-assisted medium specialization for differentiated bacterial growth. ML was remarkably significant in medium optimization for microbial and mammalian cells 21, 26 , which could be widely applied to synthetic construction and production 43, 44 . The present study provided alternative applications in medium development for selective culture.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the essential genomic sequence of modern cells, removing redundant DNA sequences from the wild-type genome in bacteria, so-called genome reduction, has been challenged to a large extent ( Kotaka et al, 2023 ; Kato and Hashimoto, 2007 ; Pósfai et al, 2006 ; Hashimoto et al, 2005 ). These efforts have been made to discover the minimal genetic requirement for a free-living organism growing under the defined conditions ( Aida and Ying, 2023 ; Breuer et al, 2019 ; Hutchison et al, 2016 ). It resulted in the finding of the coordination of genome with cell growth, that is, genome reduction significantly decreased the growth rate of Escherichia coli cells independent of culture media or growth forms ( Hitomi et al, 2022 ; Xue et al, 2021 ; Kurokawa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%